PENERAPAN METODE ENTROPY DAN TOPSIS DALAM SELEKSI MENENTUKAN OPERATOR ALAT BERAT : PENERAPAN METODE ENTROPY DAN TOPSIS DALAM SELEKSI MENENTUKAN OPERATOR ALAT BERAT - Yulianti, Henny; Nugroho, Catur (MULTINETICS, 2023)
The frequent occurrence of traffic violations is a loss for companies providing heavy equipment. This is often experienced by operators while working due to difficulties in controlling heavy equipment, the main cause being that procedures for selecting new heavy equipment operators have not been complied with. There is a need for an approach so that accepted operators can work well in operating heavy equipment and are less likely to get involved in problems when operating heavy equipment and reduce several risks of violations occurring. In solving many selection problems, such as the case that occurred, the decision support method is applied by combining 2 selection criteria approaches carried out by experts so that they can regulate the level of opinion consideration and evaluation objectively in selecting heavy equipment operators. In several writings, the value of the criteria is very dependent on the level of confidence of the experts, so that the Entropy method approach is considered to be able to calculate the weight of the criteria with accurate and objective results. The TOPSIS method is projected to select the operator that causes the least number of traffic violations by obtaining a final ranking of alternatives. The contribution of this research shows that combining these methods has an impact on operator ratings as well as reducing subjective impacts. The results obtained show that alternative A5 is ranked 1st which is recommended for acceptance due to consideration of the calculation approach process based on criteria.